﻿﻿Study of Phytotoxicity of Extracts ofIpomoea carnea Jacq. Against Sida rhombifolia Mast - A. Bhalerao, Satish (Asian Journal of Chemistry, 2010)
In present study, the allelopathic effect of Ipomoea carnea on its associate species e.g., Sida rhombifolia is studied. The growth of plant species was markedly influenced by the extracts of different parts roots, shoot and leaves of Ipomoea carnea.